2020
DOI: 10.19173/irrodl.v21i3.4784
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Online Students and the Impact of Their University Experience

Abstract: In recent decades, there has been a steady growth in the population who enter higher education in both brick-and-mortar and, in particular, online universities. This has led to an increase in heterogeneous student profiles in a relatively short period of time. The purpose of this paper was to explore the student profiles at a university that gives all its courses online, namely the Universitat Oberta de Catalunya (UOC), and analyse students’ perceptions of their university experience. With this goal in mind, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 28 publications
2
20
0
2
Order By: Relevance
“…Evidence of the effect of age and work on dropout is particularly important in the case of online universities, given the specific profile of students there. Several empirical studies have shown that the probability of participating in online universities is higher among older students (Ortagus, 2017), students who combine their studies with a full-time job (Cavanaugh & Jacquemin, 2015), and students with multiple responsibilities such as family and work (Sánchez-Gelabert et al, 2020).…”
Section: Trajectories In Higher Education Non-traditional Students and University Typementioning
confidence: 99%
See 1 more Smart Citation
“…Evidence of the effect of age and work on dropout is particularly important in the case of online universities, given the specific profile of students there. Several empirical studies have shown that the probability of participating in online universities is higher among older students (Ortagus, 2017), students who combine their studies with a full-time job (Cavanaugh & Jacquemin, 2015), and students with multiple responsibilities such as family and work (Sánchez-Gelabert et al, 2020).…”
Section: Trajectories In Higher Education Non-traditional Students and University Typementioning
confidence: 99%
“…First, it is a growing reality in the higher education system. Second, and more importantly, the characteristics of non-traditional students differ from those of their traditional peers, the importance of which lies in the impact this has on different dimensions, such as entry motivations (Dos Santos, 2020;Sánchez-Gelabert et al, 2020), dedication to studies (Safford & Stinton, 2016), experiences during university, and educational outcomes (Choi & Park, 2018).…”
Section: Trajectories In Higher Education Non-traditional Students and University Typementioning
confidence: 99%
“…A second step, given the current post-pandemic scenario could be useful to look at innovative models from other industries in which service is provided by machines (for example driver-less cars, chat bot customer service, self-service banking and automated tax returns, etc.). This growing set of digital tools used effectively by online universities may provide pedagogical, institutional, and technical support to students (chatbots, web tools, student access to their own and comparative student data analytics), which according to Salmon (2013), could favour the experience of the student body in virtual learning environments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the UOC supports its pedagogical commitment with evaluative flexibility and the creation of a learning environment that favours interactivity and cooperation between students, and between students and the university (Sánchez-Gelabert, Valente & Duart, 2020). It is a model focused on accommodating the contemporary students as active participants in their learning processes (Kocdar et al, 2018) [4] .…”
Section: The Student In Virtual Learning Environmentsmentioning
confidence: 99%
“…However, they still need to acquire specific knowledge and skills that are applicable to their personal and professional lives (McKnight et al, 2016). In addition, it is usually students with professional experience and digital skills, who generally seek an education that allows them to integrate their previous knowledge, with new skills and knowledge (Jung, 2011;Sánchez-Gelabert et al, 2020) while adapting to their emergent needs in their professional and personal lives.…”
Section: The Student In Virtual Learning Environmentsmentioning
confidence: 99%